(untitled) (Revista revoluciones, 2025)
The intrusion of foreign paramilitary groups into Venezuelan territory has generated the phenomenon known as the forced recruitment of individuals, through which persons are incorporated into the context of armed activities. Among the vulnerable groups affected by the forced recruitment carried out by irregular armed organizations, the Indigenous population stands out. For this reason, the general objective of this article is to understand the extent of the violation of Venezuela’s international protection duties toward its Indigenous peoples in the face of their forced recruitment by paramilitary groups within the country. Accordingly, a documentary research was conducted using a qualitative approach, with the aim of understanding the selected phenomenon. The findings confirm that the forced recruitment of Indigenous individuals occurs for various reasons, including explicit violence and structural violence. It is concluded that the Venezuelan State has the duty to adopt appropriate measures to reverse this situation and to demonstrate compliance with its international legal obligations.